Development of a Code of Practice and Indicators for Quality Management of Official Statistics in Thailand - Mekbunditkul, Titirut; Phisalbutr, Sorachai (Journal of Reviews on Global Economics, 2017)
This paper is concerned with the National Statistical Office of Thailand, and constructs a Code of Practice and indicators for quality management of official statistics in Thailand. Official statistics for quality management from three international agencies include the United Nations Statistics Division (UNSD), European Statistical System (Eurostat), and International Monetary Fund (IMF). Factor analysis is used to determine the important indicators and their respective weights. The research shows that a Code of Practice for quality management of official statistics in Thailand should be comprised of 9 rules and 35 common indicators.